2013
DOI: 10.1007/s11356-013-2154-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the applicability of a “toolbox” designed for microbially assisted phytoremediation: the case study at Ingurtosu mining site (Italy)

Abstract: The paper describes the fieldwork at the Italian test site of the abandoned mine of sphalerite and galena in Ingurtosu (Sardinia), with the aim to assess the applicability of a "toolbox" to establish the optimized techniques for remediation of soils contaminated by mining activities. A preliminary characterization-including (hydro)geochemistry, heavy metal concentration and their mobility in soil, bioprospecting for microbiology and botany-provided a data set for the development of a toolbox to deliver a micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…In other studies, it was confirmed that beyond Biolog EcoPlate derived values other microbial parameters, such as fast-growing heterotrophic bacterial cell number, microbial abundance, the activity of selected enzymes (dehydrogenase, urease) were also improved after red mud treatment (Castaldi et al, 2009, Garau et al, 2007. Sprocati et al 2014 explained the high functional diversity of the metabolic profile of toxic metal polluted soil gained after Viromine™ (a red mud derived product) treatment as related with the increase in pH caused by its the addition. Garau et al, 2007 found that the microbial population from the 4 w/w% RM amended Pb, Cd and Zn polluted sandy soil showed higher substrate richness measured by Biolog EcoPlate compared to the control soil while RM decreased significantly the solubility of Pb, Cd and Zn, which was likely responsible for the promotion of bacterial abundance.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In other studies, it was confirmed that beyond Biolog EcoPlate derived values other microbial parameters, such as fast-growing heterotrophic bacterial cell number, microbial abundance, the activity of selected enzymes (dehydrogenase, urease) were also improved after red mud treatment (Castaldi et al, 2009, Garau et al, 2007. Sprocati et al 2014 explained the high functional diversity of the metabolic profile of toxic metal polluted soil gained after Viromine™ (a red mud derived product) treatment as related with the increase in pH caused by its the addition. Garau et al, 2007 found that the microbial population from the 4 w/w% RM amended Pb, Cd and Zn polluted sandy soil showed higher substrate richness measured by Biolog EcoPlate compared to the control soil while RM decreased significantly the solubility of Pb, Cd and Zn, which was likely responsible for the promotion of bacterial abundance.…”
Section: Discussionmentioning
confidence: 62%
“…Due to the combined presence of ferric, aluminium and tectosilicate-like compounds in red mud (Gadepalle et al, 2007), it is proved to be an effective amendment in reducing metal mobility in contaminated soils and stimulating microbial abundance, diversity and activity (Garau et al, 2007, Lombi et al, 2002, Gray et al, 2006, Bertocchi et al, 2006, Castaldi et al, 2009, Sprocati et al, 2014.…”
mentioning
confidence: 99%
“…Our aim in this study is not to push the system to known toxic levels or to test the effect of Hg on plant production. Many fungi can tolerate high concentrations of heavy metals, especially mycorrhizae (Orlowska et al 2013), and endophytes (Shen et al 2013) or as part of a microbial toolbox (Gadd 2004; Sprocati et al 2014) targeted for bioremediation. Instead, we selected ambient and elevated Hg values to better understand the effects of Hg atmospheric deposition on the fungal phylloplane community of a more natural system.…”
Section: Introductionmentioning
confidence: 99%
“…Reclamation of AMLs using FRA could restore these lands' capabilities to provide forest-based ecosystem services such as wood production, atmospheric carbon sequestration, wildlife habitat, watershed protection and water quality protection to a greater extent than conventional reclamation practices. In fact, microbially-assisted phytoremediation (Sprocati et al 2014) could be one among the suitable approaches to reclaim AMLs; however, studies are not available to the best of our knowledge in this aspect.…”
mentioning
confidence: 99%